2010
DOI: 10.1007/s10450-010-9287-1
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modelling of adsorption isotherms

Abstract: This paper examines the possibility to use a single neural network to model and predict a wide array of standard adsorption isotherm behaviour. Series of isotherm data were generated from the four most common isotherm equations (Langmuir, Freundlich, Sips and Toth) and the data were fitted with a unique neural network structure. Results showed that a single neural network with a hidden layer having three neurons, including the bias neuron, was able to represent very accurately the adsorption isotherm data in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…As expected, the Levenberg-Marquardt algorithm combined with Bayesian regularization technique was able to avoid overfitting problems even for an excessive number of neurons. These results are in accordance with that presented by Morse et al (2011).…”
Section: Including the Effect Of Temperaturesupporting
confidence: 96%
See 2 more Smart Citations
“…As expected, the Levenberg-Marquardt algorithm combined with Bayesian regularization technique was able to avoid overfitting problems even for an excessive number of neurons. These results are in accordance with that presented by Morse et al (2011).…”
Section: Including the Effect Of Temperaturesupporting
confidence: 96%
“…A successful training can result in ANNs that can perform tasks such as predicting an output value, classifying an object, a function approaching, and recognizing a pattern in multivariate data (Dayhoff and DeLeo 2001). Morse et al (2011) indicated the use of neural networks for modeling adsorption isotherms due to the inherent complexities of adsorption process, in which the adsorbentadsorbate interaction may depend on several conditions like temperature, pH, compositions and/or the nature of adsorbent material. As confirmed by De Laurentiis and Ravdin (1994), ANNs are able to deal with these kinds of complex interactions, such as protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alireza Rahnama et al used the open dataset to train different machine learning models to predict the hydrogen weight percent and classify metal hydrides . By setting different adsorption isotherm (Langmuir, Freundlich, Sips, Toth, and TD Toth) models parameters, Morse et al trained the neural network model by generating data from the adsorption isotherm model formulas . By using Latin hypercube sampling (LHS) with a genetic algorithm to generate data, Anna et al used a multi‐objective optimization to optimize N 2 purity and recovery by an artificial neural network (ANN)…”
Section: Introductionmentioning
confidence: 99%
“…The standard and empirical models cannot adjust for compositional varietal differences, as modeling methods are based only on physical parameters. This shortcoming can be overcome by general class nonlinear models of artificial neural network (ANN) (Morse, Jones, Thibault, & Tezel, ; Myhara & Sablani, ). These heuristic models are recognized as good tools for dynamic modeling and are a useful tool for nonparametric regression.…”
Section: Introductionmentioning
confidence: 99%